If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 6x = 7x + -4 Reorder the terms: 1 + 6x = -4 + 7x Solving 1 + 6x = -4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 1 + 6x + -7x = -4 + 7x + -7x Combine like terms: 6x + -7x = -1x 1 + -1x = -4 + 7x + -7x Combine like terms: 7x + -7x = 0 1 + -1x = -4 + 0 1 + -1x = -4 Add '-1' to each side of the equation. 1 + -1 + -1x = -4 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = -4 + -1 -1x = -4 + -1 Combine like terms: -4 + -1 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| (9x+2)=3x-22 | | 32(x-1)=-8(4x-x)+24x | | 7(x-7)=7x+14 | | (9x+2)=3x-23 | | 12m-12m=2(-12+12m)-12(10-10m) | | 3r-3=6 | | (x-4)(x^2+6x-1)= | | 20y+18x=10-18x | | 0.02(2t-7)=0.04(t+5)-0.34 | | 6.8x+2=5.8x | | m/2-1=11 | | 21=49-4(5-1w) | | 4t^2-52t+160=0 | | 2w+2(2w+6)=28 | | -9+7z+2-5z= | | k=7+9 | | 27=-9(y-5) | | 3m+(m+7n)-(2m+5n)= | | e^5k=32 | | -6u+-u= | | 5(x+1)-3(x-2)=17 | | .2k-(k+.34)=.67(k+3) | | -3(4y+1)-19=-8(y+4)+4y | | 8s+18=6(2s+3)-45 | | 2(2n+2)=7(4n+4)+4 | | X+0.3x=130 | | -(2y-3x)-x-(x+2y)= | | 3x+3y=2x+9 | | 5/6y=5-11/12y | | 2e^4x+1=4 | | (4a-b)-(a-2b)+b= | | 7a-3a-2a-a=16 |